Extended thromboprophylaxis after hip fracture surgery: Real-world evidence of direct oral anticoagulants versus low molecular weight heparin of unfractionated heparin - María Manuela Clavijo; Juan Ignacio Ruiz; Martina Rodriguez Brindicci; Paula Rodriguez; Victoria Wauters; María de los Angeles Vicente Reparaz; Alex Mountford; Micaela Monteagudo; Manuela Camarero; Claudia Erica Casali; Carolina Mahuad; Florencia Aizpurua; et al. (PLoS ONE, 2026)
Background Hip fracture surgery carries the highest postoperative risk of venous thromboembolism (VTE) among surgical populations. Guidelines recommend low molecular weight heparin (LMWH) over direct oral anticoagulants (DOACs) due to limited evidence. However, oral administration and cost considerations have led to widespread real-world use of DOACs. This study aimed to compare the effectiveness and safety of extended thromboprophylaxis with DOACs versus LMWH or unfractionated heparin (UFH) after hip fracture surgery. Methods We conducted a retrospective cohort study of adults undergoing hip fracture surgery at Hospital Alemán, Buenos Aires, Argentina (January 2011–June 2025), covered by the hospital’s healthcare insurance. Eligible patients were discharged with extended pharmacologic thromboprophylaxis (LMWH, UFH, or DOACs). Outcomes within 3 months included VTE, major or clinically relevant non-major bleeding (MB/CRNMB), and all-cause mortality. Multivariable Cox regression, Fine-Gray models, and propensity score adjustments were applied. Results Of 425 hip fractures, 340 cases (301 patients) met eligibility criteria. Extended prophylaxis used was LMWH/UFH in 102 cases and DOACs in 238. VTE occurred in 2.5% of DOAC and 3.9% of LMWH/UFH cases. MB/CRNMB occurred in 2.1% vs 5.9%, and mortality in 3.0% vs 3.9%, respectively. Adjusted hazard ratios for DOACs versus LMWH/UFH were 0.64 (95% CI, 0.16–2.49) for VTE, 0.69 (0.15–2.16) for bleeding, and 0.73 (0.22–2.37) for mortality. Conclusions In this real-world cohort, DOACs showed comparable effectiveness and safety to LMWH/UFH for extended prophylaxis after hip fracture surgery. These findings support DOACs as a potential alternative in this high-risk population, pending confirmation in prospective studies.